Modulation of macrophage cytokine profiles during solid tumor progression: susceptibility to Candida albicans infection - Camargo, Marcela Regina de [UNESP]; Venturini, James [UNESP]; Vilani-Moreno, Fatima R.; Arruda, Maria Sueli Parreira de [UNESP] (Biomed Central Ltd., 2009)
Background: In order to attain a better understanding of the interactions between opportunist fungi and their hosts, we investigated the cytokine profile associated with the inflammatory response to Candida albicans infection in mice with solid Ehrlich tumors of different degrees.Methods: Groups of eight animals were inoculated intraperitoneally with 5 x 10(6) C. albicans 7, 14 or 21 days after tumor implantation. After 24 or 72 hours, the animals were euthanized and intraperitoneal lavage fluid was collected. Peritoneal macrophages were cultivated and the levels of IFN-gamma, TNF-alpha, IL-12, IL-10 and IL-4 released into the supernatants were measured by ELISA. Kidney, liver and spleen samples were evaluated for fungal dissemination. Tumor-free animals and animals that had only been subjected to C. albicans infection were used as control groups.Results: Our results demonstrated that the mice produced more IFN-gamma and TNF-alpha and less IL-10, and also exhibited fungal clearance, at the beginning of tumor evolution. With the tumor progression, this picture changed: IL-10 production increased and IFN-gamma and TNF-alpha release decreased; furthermore, there was extensive fungal dissemination.Conclusion: Our results indicate that solid tumors can affect the production of macrophage cytokines and, in consequence, affect host resistance to opportunistic infections.